2023
DOI: 10.1136/bmjopen-2023-072877
|View full text |Cite
|
Sign up to set email alerts
|

The SEE-IT Trial: emergency medical servicesStreamingEnabledEvaluationInTrauma: study protocol for an interventional feasibility randomised controlled trial

Abstract: IntroductionAccurate and timely dispatch of emergency medical services (EMS) is vital due to limited resources and patients’ risk of mortality and morbidity increasing with time. Currently, most UK emergency operations centres (EOCs) rely on audio calls and accurate descriptions of the incident and patients’ injuries from lay 999 callers. If dispatchers in the EOCs could see the scene via live video streaming from the caller’s smartphone, this may enhance their decision making and enable quicker and more accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These comprised (i) an inner-city sub-study in an ambulance service already routinely using video livestreaming to explore the acceptability and feasibility of using video livestreaming in a more diverse population; and (ii) a staff wellbeing sub-study in an ambulance service not using video livestreaming to provide comparison to the trial staff. The full trial protocol was published once no further protocol changes were required [ 17 ]. Previous versions of the trial protocol can be found on the NIHR website, including a log of amendments [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These comprised (i) an inner-city sub-study in an ambulance service already routinely using video livestreaming to explore the acceptability and feasibility of using video livestreaming in a more diverse population; and (ii) a staff wellbeing sub-study in an ambulance service not using video livestreaming to provide comparison to the trial staff. The full trial protocol was published once no further protocol changes were required [ 17 ]. Previous versions of the trial protocol can be found on the NIHR website, including a log of amendments [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A full list of sites is provided in the trial protocol [ 17 ]. The observational inner-city sub-study was conducted in London Ambulance Service NHS Trust (LAS, including London’s Air Ambulance Charity, LAA), and the staff wellbeing sub-study was in East of England NHS Trust (EEAST).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine can be categorized, on one hand, by implemented activities (i.e., televisits, teleconsultations, and tele-healthcare cooperation), and on the other, by activity purposes, which can be summarized as follows: Remote monitoring: A variety of medical-health activities with the purpose of monitoring a patient’s health status, via the implementation of routine medical tests, the communication of medical results to healthcare professionals, and the potential transmission of automated responses [ 7 , 8 , 9 ]. The collection and sharing of clinical data, which aims to disseminate clinical information that is less sensitive to time between healthcare professionals and/or between doctors and patients, and which currently often involves a delay between the transmission, the receipt of, and the response to the content that was shared [ 10 , 11 ]. Interactive synchronous telemedicine, which includes practices involving real-time communication between doctors and patients, which may or may not involve the activity of data sharing [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The collection and sharing of clinical data, which aims to disseminate clinical information that is less sensitive to time between healthcare professionals and/or between doctors and patients, and which currently often involves a delay between the transmission, the receipt of, and the response to the content that was shared [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%